Shallow water hydroids (Cnidaria, Hydrozoa) from the 2002 NOWRAMP cruise to the Northwestern Hawaiian Islands - Calder, Dale R.; Faucci, Anuschka (Zootaxa, 2021)
Forty-two species of hydroids, excluding stylasterids, are reported in the present collection from the Northwestern Hawaiian Islands. Of these, four are anthoathecates and 38 are leptothecates. Among the latter, Sertularella affinicostata and Monotheca gibbosa are described as new species. The binomen Halopteris longibrachia is proposed as a new replacement name for Plumularia polymorpha var. sibogae Billard, 1913, an invalid junior primary homonym of P. sibogae Billard, 1911. Based largely on evidence from earlier molecular phylogenies, the genus Disertasia Neppi, 1917 is resurrected to accommodate species including Dynamena crisioides Lamouroux, 1824, Sertularia disticha Bosc, 1802, and Sia. moluccana Pictet, 1893. Sertularella robusta Coughtrey, 1876 is an invalid junior primary homonym of Sla. gayi var. robusta Allman, 1874a, and has been replaced here by the binomen Sla. quasiplana Trebilcock, 1928, originally described as Sla. robusta var. quasiplana Trebilcock, 1928. Clytia hummelincki (Leloup, 1935) is referred to the synonymy of its senior subjective synonym, C. brevithecata (Thornely, 1900). Following Reversal of Precedence provisions in the International Code of Zoological Nomenclature to preserve prevailing usage of binomena, the familiar names Sia. disticha Bosc, 1802 (also known as Dynamena disticha) and Lytocarpia phyteuma (Stechow, 1919b) are designated nomena protecta and assigned precedence over their virtually unknown senior synonyms Hydra quinternana Bosc, 1797 and Aglaophenia clavicula Whitelegge, 1899, respectively, names now reduced to the status of nomena oblita. Twenty species are reported for the first time from Hawaii [Eudendrium merulum Watson, 1985, Phialellidae (undetermined), Hebella sp., Hebellopsis scandens (Bale, 1888), H. sibogae Billard, 1942, Clytia brevithecata, C. linearis (Thornely, 1900), C. cf. noliformis (McCrady, 1859), Halecium sp., Sla. affinicostata, Sla. angulosa Bale, 1894, Pasya heterodonta (Jarvis, 1922), Tridentata orthogonalis (Gibbons & Ryland, 1989), Pycnotheca producta (Bale, 1881), Monotheca gibbosa, H. longibrachia, A. postdentata Billard, 1913, A. suensonii Jäderholm, 1896, A. whiteleggei Bale, 1888, and L. flexuosa (Lamouroux, 1816)]. Sertularia orthogonalis, reported for only the third time worldwide, is assigned to the genus Tridentata Stechow, 1920. Hydroids of the NOWRAMP 2002 collection consisted largely of presumptive widespread species, with over 75% of them having been reported elsewhere in the tropical Indo-west Pacific region.